Addressing Climate Change and Its Effects on Human Health: A Call to Action for Medical Schools. (24th November 2020) - Goshua, Anna; Gomez, Jason; Erny, Barbary; Burke, Marshall; Luby, Stephen; Sokolow, Susanne; LaBeaud, A. Desiree; Auerbach, Paul; Gisondi, Michael A.; Nadeau, Kari
Abstract : Human health is increasingly threatened by rapid and widespread changes in the environment and climate, including rising temperatures, air and water pollution, disease vector migration, floods, and droughts. In the United States, many medical schools, the American Medical Association, and the National Academy of Sciences have published calls for physicians and physicians-in-training to develop a basic knowledge of the science of climate change and an awareness of the associated health risks. The authors—all medical students and educators—argue for the expeditious redesign of medical school curricula to teach students to recognize, diagnose, and treat the many health conditions exacerbated by climate change as well as understand public health issues. In this Invited Commentary, the authors briefly review the health impacts of climate change, examine current climate change course offerings and proposals, and describe the rationale for promptly and comprehensively including climate science education in medical school curricula. Efforts in training physicians now will benefit those physicians' communities whose health will be impacted by a period of remarkable climate change. The bottom line is that the health effects of climate reality cannot be ignored, and people everywhere must adapt as quickly as possible.